KAJIAN KADAR CHOLINESTERASE DALAM DARAH OPERATOR FOGGING MENURUT MASA KERJA, LAMA PAPARAN DAN PENGGUNAAN APD DI KOTA SURABAYA - Gani AgustDini; Setiawan .; Marlik . (GEMA LINGKUNGAN KESEHATAN, 2014)
Surabaya city are scarlatina endemis area with the number of cases who are still high. Last three yearsdata, showing patient of scarlatina totality 3.379 people in 2010, 1.008 people in 2011 and 1.091 people in2012. Highest of scarlatina cases purpose in long exposure frequency pesticides to do spraying onoperators fogging the longer close fitting. Operators fogging have a risk exposure of pesticides. This willbe worse if not supported by the use of APD good and right. This research aimed to assessthe durationwork, long exposure and using of safety aparatus with cholinesterase levels on operators foggingThe kind of research used is research that is both a moment of observational (cross sectional). Datacollecting by means of observation and spread a questionnaire. An population research is the foggingguidance operator service and control a vector department of health city surabaya in the city of surabayawith the number is 70 operators fogging by samples41 responden taken in simple random sampling. Datanext presented in table form and analyzed in descriptive.The results showed that the majority of operators fogging over 3 years 70.7%, overall long exposure(100%) of less than 5 hours and as much as 78.0% operator fogging wear APD but not complete(100%)with normal cholinesterase ( 75 - 100% )With see the result of this research was then suggested to operators of the pesticide fogging shouldreduce exposure by them self, no smoking and eat / drink after if pesticides contact and always forwashing hands using soap with clean water.